The Empirical Economic Growth Literature - Raymond J.G.M. Florax; Henri L.F. de Groot; Reinout Heijungs (Tinbergen Institute, 2002)
The empirical economic growth literature is criticized for its lack ofrobustness. For different definitions of robustness, conclusions vary from 'almost everycorrelation is fragile' to 'a substantial number of explanatory variables are robust.' Were-analyze the empirical results of the economic growth literature for various alternativedefinitions of robustness using quasi-experiments. The analysis pertains to sign, size andsignificance of the effects, and we relax the quasi-experimental procedure by no longerapplying a set of 'fixed' variables. Response surface analyses of the quasi-experimentsreveal that the number of robust variables is limited, the effects crucially depend on thespecification of conditioning variables, and the default specification based on theconvergence/catch-up model is associated with estimated effects of conditioning variablesthat constitute outliers.
Keywords: C52; C90; O11; O40; 330; economic growth; sensitivity analysis; robustness; response surface.; Wirtschaftsforschung; Wirtschaftswachstum; Empirische Methode; Sensitivitätsanalyse; Robustes Verfahren; Theorie